Effect of Endophyte Association with Brachiaria Species on Shoot and Root Morpho-physiological Responses under Drought Stress - Odokonyero, Kennedy; Acuña, Tina Botwright; Cardoso Arango, Juan Andrés; Jiménez Serna, Juan de la Cruz; Rao, Idupulapati M. (OMICS Publishing Group, 2017)
A greenhouse experiment was conducted at the International Centre for Tropical Agriculture in Colombia to evaluate effects of the fungal endophyte, Acremonium implicatum, on growth and physiological responses of five Brachiaria cultivars. Plants were grown under well-watered (WW) and drought-stressed (DS) conditions, with (E+) and without (E-) endophyte; and their morpho-physiological responses were determined. Significant two-way and three-way interactions produced variable effects on leaf area, number of tillers, shoot elongation, shoot biomass, total root diameter, diameter of cortex, area of stele and diameter of xylem vessel. Main effect of endophyte significantly increased leaf stomatal conductance and reduced diameter of xylem. Smaller leaf area was found in endophyte-infected than control plants of three cultivars, both under WW and DS conditions, which indicates a cost of endophyte infection to the host cultivars. Large root diameter and area of stele under WW conditions, as well as small diameter of xylem vessels in some cultivars suggests that endophyte may improve efficiency for water uptake and use under different water regimes. Less Root Cortical Aerenchyma (RCA) was observed in endophyte-infected plants of Tully and Cayman than the control, which may influence plant capacity for resource acquisition in Brachiaria. Genotype-specific variation among hosts generally segregated the cultivars in terms of their shoot and root responses, based on presence (E+) or absence (E-) of endophyte. However, future studies should examine how association of A. implicatum with Brachiaria grass affects capacity for water uptake and carbon accumulation, and the role of RCA in these processes.